Validation of The Slovenian Version of the Low Anterior Resection Syndrome Score for Rectal Cancer Patients after Surgery - Grosek, Jan (Zdr Varst, 2019)
PURPOSE: The purpose of this study was to translate the low anterior resection syndrome (LARS) score into Slovenian and to test its validity on Slovenian patients who underwent low anterior rectal resection. METHODS: The LARS score was translated from English into Slovenian and then back-translated following international recommendations. The Slovenian version of the LARS questionnaire was completed by patients who underwent low anterior rectal resection between 1 January 2006 and 31 December 2010 at the University Medical Centre Ljubljana. An anchor question assessing the impact of bowel function on lifestyle was included. To assess test-retest reliability, some of the patients answered the LARS score questionnaire twice. RESULTS: A total of 100 patients (66.7%) of the 150 patients who were contacted for participation, were included in the final analysis. A total of 58 patients reported major LARS score. The LARS score was able to discriminate between patients who received radiotherapy and those who did not (p<0.001), and between total and partial mesorectal excision (p<0.001). Age was not associated with a greater LARS score (p=0.975). There was a perfect fit between the QoL category question and the LARS score in 66.0% of cases and a moderate fit was found in 24.0% of the cases, showing good convergent validity. Test-retest reliability of 51 patients showed a high intraclass correlation coefficient of 0.86. CONCLUSIONS: The Slovenian translation of the LARS score is a valid tool for measuring LARS.